Whole genome sequencing and comparative analysis of a novel Chlamydia psittaci strain. Issue 5 (27th May 2022) - Livingstone, Morag; Ribeca, Paolo; Beeckman, Delphine; Ende, Arie van der; Pannekoek, Yvonne; Vanrompay, Daisy; Longbottom, David
Abstract : Background: Chlamydia abortus and Chlamydia psittaci are important pathogens of livestock and avian species, respectively. While C. abortus is recognized as descended from C. psittaci species, there is emerging evidence of strains that are intermediary, including C. psittaci strain 84/2334 that was isolated from a parrot. Methods: Strain 84/2334 was analysed by multi-locus sequence typing of seven housekeeping genes and by analysis of five species-discriminant proteins. The strain was de novo sequenced for comparison with representative strains from chlamydial species. 16S rRNA and whole genome phylogenetic analyses, network and recombination analyses, and analyses of key virulence-associated genes were conducted to explore its evolutionary relationship with both C. psittaci and C. abortus. Results: Typing, 16S rRNA and whole genome phylogenetic analyses, as well as network and recombination analyses showed that strain 84/2334 clusters closely with C. abortus. Analyses also suggested a closer evolutionary relationship with classical C. abortus strains, than to two other avian C. abortus or C. psittaci strains. Analyses of virulence-associated genes that exhibit greatest diversity within chlamydial species, reveal greater diversity than present in sequenced C. abortus genomes. The strain also possesses an extrachromosomal plasmid, as found in C. psittaci species but absent from all sequenced classical C. abortus strains. Conclusion: The results are consistent with 84/2334 being a C. abortus ancestral strain, suggesting that it should be reclassified as C. abortus. The identification of a C. abortus strain bearing an extra-chromosomal plasmid has implications for plasmid-based transformation studies providing a potential route for future vaccine development.